INTEGRATION OF MODERN PSYCHOLOGICAL TECHNOLOGIES OF EMOTIONAL REGULATION IN THE DEVELOPMENT OF ACADEMIC ACHIEVEMENTS OF ADOLESCENTS (Psychology Travelogs, 2025)
The article examines the development of emotional regulation and academic self-regulation in adolescents as key factors of psycho-emotional well-being and academic success. Adolescence involves high sensitivity to stress, cognitive and emotional changes, and increased academic demands, creating risks of anxiety, emotional exhaustion, and reduced learning motivation. The study explores the impact of psychotechnologies for emotional regulation on academic performance. Dysfunctional cognitive beliefs-such as perfectionism, dependence of self-esteem on external evaluation, error catastrophizing, and unrealistic demands-were analyzed in relation to emotional regulation and learning effectiveness. Results showed that successful adolescents exhibit flexible thinking, constructive reappraisal, and tolerance for uncertainty and mistakes, while less successful students display dysfunctional beliefs and impulsive emotional behavior, lowering motivation and productivity. Based on these findings, a psychological program was developed to enhance emotional regulation and academic self-regulation, incorporating interactive exercises, role-playing, reflective journals, and psychoeducational materials. The program fosters awareness of emotions, cognitive strategies, and self-regulation skills. Evaluation revealed significant reductions in dysfunctional beliefs and anxiety, alongside improvements in self-control, cognitive flexibility, and learning motivation. These findings confirm that psychotechnologies for emotional regulation support the development of adaptive cognitive and behavioral resources, enhance academic outcomes, and promote psycho-emotional well-being in adolescents, providing an effective tool for supporting students with high emotional reactivity and low motivation.
Keywords: emotional regulation; academic self-regulation; cognitive strategies; psychotechnologies; adolescents